PENDAFTARAN HAK ATAS TANAH BEKAS TANAH PARTIKELIR KELURAHAN KLENDER JAKARTA TIMUR: Karsiti - admin, admin (Reformasi Hukum, 2017)
Private land based on Act number 1 of 1958 concerning the Elimination of Particular Land is deleted and then the private land becomes state land in accordance with the provisions of the Regulation Minister of Agrarian Affairs (PMNA) Number 9 of 1999 concerning Procedures for Granting and Cancellation of State Land Rights and Management Rights. In connection with this, the authors formulate the problem, namely: (1). Why is there no legal certainty regarding ownership of the rights to the former private land; (2). What are the procedures for registering rights to land of ex-private lands and any obstacles to the registration of rights to ex-private lands; So the author managed to get a conclusion, namely: 1). The community in Klender Village does not yet know about the legal certainty regarding the ownership of the ex-land of the land, namely the certainty of the owner, the certainty of the location of the land, the certainty of the boundaries, and the certainty of the land area. This is the reason for the community in the Klender Village to apply for land rights because: Requires proof of legal land rights to land ownership and other reasons because these private lands have not been recorded by the East Jakarta City Administration Land Office. 2). In registering rights to ex-private land, several obstacles were encountered, in this case it could be caused by legal regulatory factors where the legal regulations governing it were felt by the community there were still too many requirements to be fulfilled, and economic factors meant that all matters needed money because if the applicant does not have enough money, then usually the application file is confined to the settlement.